A Modeling Assessment of Large-Scale Hydrologic Alteration in South American Pantanal Due to Upstream Dam Operation - Jardim, Pedro Frediani; Melo, Maria Marcella Medeiros; Ribeiro, Larissa de Castro; Collischonn, Walter; Paz, Adriano Rolim da (Frontiers in Environmental Science, 2020)
Natural river flow provides the conditions required to sustain freshwater ecosystems, and the greater the departure from the natural regime, the greater the loss of those ecosystems. In South America, new hydropower dams are continuously being constructed and planned in regions within and around the Amazon basin and in the Upper Paraguay river basin, a region notable for the Pantanal, a huge wetland ecosystem that is largely dependent on the flow regime of the Paraguay river and its tributaries. In this context, it is meaningful to examine the hydrological changes caused by the major Manso dam, that is operating since 2001 at the headwaters of one of the major tributaries of the Paraguay river. This was done for the same case study by other authors in previous studies using only gauging stations data. However, those previous assessments were limited due to the confounding effects of climate variability and the necessity of relatively long term observed time series. Here, we applied a modelling approach to evaluate the changes in hydrological regime caused by Manso dam operation. Our modelling approach was based on the combination of the MGB large-scale hydrologic model with the SIRIPLAN large-scale wetland model. The models were applied, using river reaches from 2 to 10 km, in two scenarios during the period from 2003 to 2015. In the first scenario we used naturalized streamflow at the dam site as input to the hydrological model. In the second scenario we used observed reservoir outflow time series as input to the hydrological model. Our results show that Manso dam has a regulation effect that decreases high flows, increases low flows and reduces lateral connectivity. The decrease in high flows is limited to the region upstream of the Pantanal floodplain, while increase in low flows extends into Pantanal. Timing of maximum and minimum flows is less affected, except for the river reach immediately downstream of the dam. Our results improve the assessment of spatial patterns of hydrologic alteration, giving more confidence in the assessment of magnitude and spatial extension of the effects of Manso dam in the Pantanal region.